Ethical Climate, Job Satisfaction, and Organizational Commitment of Hotel Employees - Carmen C. Menes; Ismael A. Haguisan III (Philippine Social Science Journal, 2020)
Ethical climate in the workplace has a relationship with job satisfaction and organizational commitment; thus, influencing organizational productivity. This descriptive-correlational study confirmed the relationship between ethical climate, job satisfaction, and hotel employees’ organizational commitment. Using stratified random sampling proportionate allocation, 152 employees from two hotels with the same owner and management were identified as respondents. An adapted-modified survey questionnaire was used to collect the data.  Mean, standard deviation, and Pearson r were used to analyze the data. The employees in the standard class hotels perceived an ethical work environment.  They were slightly satisfied and committed to their job. Their perceived ethical climate showed a significant relationship with job satisfaction and organizational commitment. The management may explore various ways to improve the ethical climate, job satisfaction, and organizational commitment of employees to attain higher productivity.